2018
DOI: 10.1021/acs.langmuir.7b03622
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption of a Protein–Nanocarrier Complex onto Cell Membranes through a High Freeze Concentration by a Polyampholyte Cryoprotectant

Abstract: The transportation of biomolecules into cells is of great importance in tissue engineering and as stimulation for antitumor immune cells. Previous freezing strategies at ultracold temperatures (-80 °C) used for intracellular transportation exhibit certain limitations such as extended time requirements and harsh delivery system conditions. Thus, the need remains to develop simplified methods for safe nanomaterial delivery. Here, we demonstrated a unique strategy based on the ice-crystallization-induced freeze c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…This membrane interaction has also been exploited by Matsumura for the introduction of lysozyme proteins into cells through a freeze–thaw mechanism, which enables a 4-fold increase in uptake when compared to nonfrozen cells . It was then demonstrated that these ampholyte-based nanocarrier complexes allowed more protein internalization when compared to 10% DMSO, which is known to enhance membrane permeability . Taken together, these results suggest that while also providing superior cell viability post-thaw, polyampholytes interact with the cell membrane during the freezing process to allow greater payload uptake when incorporated into a protein–nanocarrier complex.…”
Section: Introductionmentioning
confidence: 87%
“…This membrane interaction has also been exploited by Matsumura for the introduction of lysozyme proteins into cells through a freeze–thaw mechanism, which enables a 4-fold increase in uptake when compared to nonfrozen cells . It was then demonstrated that these ampholyte-based nanocarrier complexes allowed more protein internalization when compared to 10% DMSO, which is known to enhance membrane permeability . Taken together, these results suggest that while also providing superior cell viability post-thaw, polyampholytes interact with the cell membrane during the freezing process to allow greater payload uptake when incorporated into a protein–nanocarrier complex.…”
Section: Introductionmentioning
confidence: 87%
“…Cryopreservation of living cells and tissues became fundamental in biotechnology, plant programmes, and modern medicine. Increasing problems associated with human reproduction put techniques of assisted reproduction, including in vitro fertilization (IVF), to the center of human medicine. In the frame of IVF, embryos and sperm are deeply frozen prior to being mutually coupled, cultured, checked for possible defects, and implanted.…”
Section: Introductionmentioning
confidence: 99%
“…Polyampholytes including zwitterionic polymers also show promise in several other biomedical applications such as for cell preservation, antibiofouling, and tissue engineering. , These polyelectrolytes contain both cationic and anionic charges in the polymeric backbone. We previously developed new hydrophobic polyampholytes that can form self-assembled nanoparticles and efficiently transfer protein-based materials to the cytosol of cells. These hydrophobic polyampholytes were easily designed by modifying the anionic functional group dodecylsuccinic anhydride (DDSA) and a large amount of succinic anhydride (SA) in ε-poly- l -lysine (PLL), which confers the hydrophobic polyampholytes with an anionic charge. Although hydrophobicity can enhance cell membrane affinity, it is nevertheless difficult to internalize proteins inside cells because of the negatively charged surface potential.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrophobicity can enhance cell membrane affinity, it is nevertheless difficult to internalize proteins inside cells because of the negatively charged surface potential. Thus, to achieve efficient delivery to cells, we also developed a novel low temperature-based freeze-concentration approach to act as a driving force to internalize materials inside cells efficiently. Freeze concentration is a physicochemical phenomenon wherein water molecules are crystallized into ice so that the solutes present in the system are ejected, which thereby enhances the concentration. The increased concentration occurs across the periphery of the cell membrane resulting in adsorption of solutes.…”
Section: Introductionmentioning
confidence: 99%